Sunday
March 26, 2017

Post a New Question

Posted by on .

x^2-7x = 0
substitue x=7 into the equatiopn and explain why this shows that x=7 is the solution.

ok so i do this: if x=7 then the equation becomes
7^2-49=0
7^2=49
49-49=0
so x=7 is correct (is that explanation enough?)

now i have to write out a complete solution to the orginal equation - i thought i had already done that above, could someone help me out please!

  • maths - ,

    the solution:
    x^2 - 7x = 0
    x(x-7) = 0
    so x = 0 or x = 7

    the check:
    if x = 0
    LS = 0^2 - 7(0) = 0
    RS = 0
    so x = 0

    if x = 7
    LS = 7^2 - 7(7) = 49-49 = 0
    RS = 0
    so x = 7

    x = 0 or x = 7


    (The correct way to verify a solution is to show for the given value that the original left side (LS) is equal to the original right side (RS) of the equation. )

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question